IMPLIKASI HUKUM TERHADAP PERKAWINAN ANAK DI BAWAH UMUR - Halda Septiana Purwinarto; Bima Romadiansyah (Universitas Muhammadiyah Ponorogo, 2022)
This research aims to find out the age limit for the marriage of minors and the legal implications of child marriage. The method used is a normative legal research method, namely researching or studying existing legal norms related to marriage. In contrast, the scope of this research includes the marriage of minors. In the discussion in this study related to the age limit, many occur in Indonesia. Customary areas in Indonesia often carry out child marriages. The following talk discusses the legal implications of carrying out underage marriages. Mental readiness factors, education, social and economic factors influence children who marry underage. Because their mental readiness is not sufficient, they will have problems in the future that will have legal implications or implications for them. The legal consequences of marriage for minors impact the married couple themselves. The level of children's education has decreased, the economic level is low, the level of mental readiness and legal skills that have been carried for children who have married so that they cannot account for themselves as legal subjects. They have not been able to account for their actions before the law if a problem occurs because their mental readiness is insufficient to carry out a marriage.